Fuzzy Logic-Based Paddy Field Irrigation Control Using pH, Moisture, and Water Level - Muhammad Sulthan Alfriansyah; Setya Mega Bagaskara; Ghazy Hassan; Chika Hayya Sabillah; Muhammad Faiz Assariy; Rizki Achmad Rifa'i Dwi Warno (Batrisya Education, 2026)
Efficient irrigation management is a crucial factor in increasing rice agricultural productivity and maintaining water resource sustainability. Conventional irrigation systems, which are still manually controlled, often lead to water waste, unstable soil moisture, and inappropriate water pH levels for plant growth. This research aims to design and implement a fuzzy logic-based rice field irrigation control system by considering three primary parameters: soil moisture, water level, and irrigation water pH. The system utilizes an Arduino Uno microcontroller integrated with a soil moisture sensor, an HC-SR04 ultrasonic sensor, and a pH sensor. The Mamdani Fuzzy Method is employed as the inference system to determine the opening angle of the water gate controlled by a servo motor. The rule base consists of 27 rules derived from the combination of three linguistic sets for each input variable. The defuzzification process uses the Centroid method to generate a crisp value in the form of the servo angle. The test results demonstrate that the system is capable of adaptively regulating water flow based on soil conditions and water quality, thereby reducing the risk of over-irrigation or under-irrigation. The proposed system exhibits more flexible performance compared to conventional threshold-based systems.